The Effect of Calcium Channel Blockers on Vascular Remodeling and Intra-Renal Hemodynamics in Chronic Kidney Disease - Kuchkarova Shahnoza Anvarovna; Keldiyorov Botir Shokir o’g’li (Zien Journals, 2024)
Comparative assessment of the effect of calcium channel blockers amlodipine andlercanidipine on functional status of kidneys, intrarenal hemodynamics and vascular system remodeling inpatients with stage III of chronic kidney disease
Keywords: Chronic Kidney Disease; Glomerulosclerosis; Calcium Channel Blockers